Caffeine and anaerobic. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n5p602 - Bruno Honorato da Silveira; Rafael Alves de Aguiar; Tiago Turnes; Fabrizio Caputo (Universidade Federal de Santa Catarina, 2012)
The ergogenic effect of caffeine on anaerobic exercises remains controversial. Such effect seems to depend on exercise duration, test protocol, and training status of the subjects studied. Thus, the objective of this review of the literature was to analyze studies investigating the effect of caffeine on the performance of anaerobic exercises and to discuss the different methods used to measure this effect in order to try to explain controversial results, as well as to present possible mechanisms of action of caffeine. During anaerobic exercises lasting less than 30 seconds, caffeine appears to have an influence only on the performance of athletes; however, there is need of further studies with this population. Nevertheless, in longer exercises (from 60 to 180 seconds), caffeine seems to improve performance regardless of the training status. The mechanism of action remains unclear; however, there is evidence that the action of caffeine is multifactorial, since this substance changes central and peripheral characteristics. Among the main characteristics, caffeine acts as an adenosine receptor antagonist, increasing the excitability of the central nervous system and changing the perception of effort and pain, in addition to reducing the sensitivity of the sarcoplasmic reticulum during calcium release. Further studies investigating the role of caffeine in anaerobic exercises should be conducted using anaerobically trained individuals and protocols similar to those of cyclic sports in order to clarify the contradictory results.